Does operational sex ratio influence relative strength of purging selection in males versus females?. (10th October 2019) - Plesnar‐Bielak, Agata; Sychta, Karolina; Gaczorek, Tomasz S.; Palka, Joanna K.; Prus, Monika A.; Prokop, Zofia M.
Abstract: According to theory, sexual selection in males may efficiently purge mutation load of sexual populations, reducing or fully compensating 'the cost of males'. For this to occur, mutations not only need to be deleterious to both sexes, they also must affect males more than females. A frequently overlooked problem is that relative strength of selection on males versus females may vary between environments, with social conditions being particularly likely to affect selection in males and females differently. Here, we induced mutations in red flour beetles ( Tribolium castaneum ) and tested their effect in both sexes under three different operational sex ratios (1:2, 1:1 and 2:1). Induced mutations decreased fitness of both males and females, but their effect was not stronger in males. Surprisingly, operational sex ratio did not affect selection against deleterious mutations nor its relative strength in the sexes. Thus, our results show no support for the role of sexual selection in the evolutionary maintenance of sex. Abstract : In sexual populations, sexual selection in males can purge mutation load and reduce "the cost of males" if mutations are deleterious to both sexes and their effect on males is stronger than that on females. In our study in red flour beetle, induced mutations decreased fitness of both sexes, but their effect was not stronger in males, providing no support for the role of sexual selection in the evolutionary maintenance of sex. Moreover, selection against deleterious mutations and its relative strength in males and females was not affected by population sex ratio.